From theories to media: towards a generalization of business cultures - Afsin, Erol Nathan Yasin (2016)

(untitled)
This study attempts to examine how cultural stereotypes on American and Japanese businesspersons, two national groups opposed in terms of cultural attributes, are represented and kept over time within the media. Further, how the media use cultural assumptions found in theories to generalize their representations is investigated. With an emphasis on contents along with systematic observations, the research is conducted through a dual analysis combining 32 recent Internet websites and the film Gung Ho (1986). The data are categorized according to four cultural dimensions (power distance index; individualism versus collectivism; low context versus high context cultures; monochronic versus polychronic cultures) from Hofstede (2001) Hall’s (1976) frameworks on national business cultures. The findings show that stereotypes on business cultures are not only repeated and interrelated among sources but also deeply embedded over space and time. Representations have been categorized and simplified to some traits, key attitudes and behaviours according to the membership of a national group, and the information shared are mainly homogeneous and stagnant. This study is an attempt to contribute to understand how old theories may still shape the intercultural business field in a stereotypical logic through ideological assumptions displayed by media channels over time. As the media may play a significant role in influencing managers’ mental representations, recommendations regarding how they could deal with such cultural stereotypes while conducting business are provided.